Partially-coupled least squares based iterative parameter estimation for multi-variable output-error-like autoregressive moving average systems - Ma, Hao; Pan, Jian; Ding, Feng; Xu, Ling; Ding, Wenfang (IET control theory & applications, 2019)
This study considers the parameter estimation of a multi-variable output-error-like system with autoregressive moving average noise. In order to solve the problem of the information vector containing unknown variables, a least squares-based iterative algorithm is proposed by using the iterative search. The original system is divided into several subsystems by using the decomposition technique. However, the subsystems contain the same parameter vector, which poses a challenge for the identification problem, the approach taken here is to use the coupling identification concept to cut down the redundant parameter estimates. In addition, the recursive least squares algorithm is provided for comparison. The simulation results indicate that the proposed algorithms are effective.